2020
DOI: 10.1128/jvi.01688-19
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Differences between Closely Related Reovirus T3D Lab Strains Alter Oncolytic Potency In Vitro and In Vivo

Abstract: Little is known about how genetic variations in viruses affect their success as therapeutic agents. The type 3 Dearing strain of Mammalian orthoreovirus (T3D) is undergoing clinical trials as an oncolytic virotherapy. Worldwide, studies on reovirus oncolysis use T3D stocks propagated in different laboratories. Here, we report that genetic diversification among T3D stocks from various sources extensively impacts oncolytic activity. The T3D strain from the Patrick Lee laboratory strain (TD3PL) showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Over the course of propagation in different laboratories, these strains have accumulated 20 amino acid polymorphisms. Surprisingly, despite only small genomic divergence, the T3D lab strains exhibit drastic differences in their ability to replicate in tumorigenic cells in vitro, and exhibit oncolytic activities in vivo [19,20]. Classical and reverse genetics approaches previously revealed that five polymorphisms dispersed among S4, M1, and L3 reovirus genes account for the oncolytic differences between T3D strains.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the course of propagation in different laboratories, these strains have accumulated 20 amino acid polymorphisms. Surprisingly, despite only small genomic divergence, the T3D lab strains exhibit drastic differences in their ability to replicate in tumorigenic cells in vitro, and exhibit oncolytic activities in vivo [19,20]. Classical and reverse genetics approaches previously revealed that five polymorphisms dispersed among S4, M1, and L3 reovirus genes account for the oncolytic differences between T3D strains.…”
Section: Discussionmentioning
confidence: 99%
“…Together the data supports the following model: T3D TD induces more IFN signalling than T3D PL because of slower replication kinetics, rather than that IFN signalling being the cause of reduced T3D TD replication kinetics. In other words, T3D PL inherently replicates better than T3D TD through mechanisms independent of IFN; some of these mechanisms were previously described and include inherently better transcription activity by T3D PL particles [19,20]. However, since IFNs can suppress cell-cell spread, the induction of IFNs by T3D TD further suppresses dissemination of this T3D stain, producing an even-larger differential between T3D TD and T3D PL in IFN-proficient cells.…”
Section: Plos Pathogensmentioning
confidence: 95%
See 3 more Smart Citations